Formulario para Antiderivadas
Formulario para Antiderivadas
Formulario para Antiderivadas
Ver Pag.268-274
1) ∫ 𝑑𝑥 = 𝑥 + 𝐶 ,
2) ∫ 𝐾𝑑𝑥 = 𝐾𝑥 + 𝐶 , K es una contante cualquiera.
𝑥 𝑛+1 1 (𝑎𝑥+𝑏)𝑛+1
3) ∫ 𝑥 𝑛 𝑑𝑥 = + 𝐶, 𝑛 ≠ −1 3) ∫(𝑎𝑥 + 𝑏)𝑛 𝑑𝑥 = +𝐶
𝑛+1 𝑎 𝑛+1
1
4) ∫ 𝑒 𝑥 𝑑𝑥 = 𝑒 𝑥 + 𝐶 4) ∫ 𝑒 𝑎𝑥 𝑑𝑥 = 𝑒 𝑎𝑥 + 𝐶
𝑎
𝑏𝑥 1 𝑏𝑎𝑥
5) ∫ 𝑏 𝑥 = +𝐶 5) ∫ 𝑏𝑎𝑥 𝑑𝑥 = +𝐶
𝑙𝑛𝑏 𝑎 𝑙𝑛𝑏
1 𝑑𝑥 1 𝑑𝑥 1
6) ∫ 𝑑𝑥 o ∫ = 𝑙𝑛|𝑥| + 𝐶 6) ∫ 𝑑𝑥 o ∫ 𝑑𝑥 = ln(𝑎𝑥 + 𝑏)+C
𝑥 𝑥 (𝑎𝑥+𝑏) (𝑎𝑥+𝑏) 𝑎
−1
7) ∫ 𝑠𝑒𝑛𝑥 𝑑𝑥 = −𝑐𝑜𝑠𝑥 + 𝐶 7) ∫ 𝑠𝑒𝑛(𝑎𝑥 ) 𝑑𝑥 = cos(𝑎𝑥 ) + 𝐶
𝑎
1
8) ∫ 𝑐𝑜𝑠𝑥 𝑑𝑥 = 𝑠𝑒𝑛𝑥 + 𝐶 8) ∫ 𝑐𝑜𝑠𝑎𝑥 𝑑𝑥 = 𝑠𝑒𝑛𝑎𝑥 + 𝐶
𝑎
−1
9) ∫ 𝑡𝑎𝑛𝑥 𝑑𝑥 = − ln|𝑐𝑜𝑠𝑥| + 𝐶 9) ∫ tan(𝑎𝑥) 𝑑𝑥 = 𝑙𝑛|cos(𝑎𝑥)| + 𝐶
𝑎
1
o = ln|𝑠𝑒𝑐𝑥| + 𝐶 o = 𝑙𝑛|sec(𝑎𝑥)| + 𝐶
𝑎
1
10) ∫ 𝑐𝑜𝑡𝑥 𝑑𝑥 = 𝑙𝑛|𝑠𝑒𝑛𝑥| + 𝐶 10) ∫ 𝑐𝑜𝑡𝑎𝑥 𝑑𝑥 = 𝑙𝑛|𝑠𝑒𝑛𝑎𝑥| + 𝐶
𝑎
1
11) ∫ sec 𝑥 𝑑𝑥 = 𝑙𝑛|𝑠𝑒𝑐𝑥 + 𝑡𝑎𝑛𝑥| + 𝐶 11) ∫ sec 𝑎𝑥 𝑑𝑥 = 𝑙𝑛|𝑠𝑒𝑐𝑎𝑥 + 𝑡𝑎𝑛𝑎𝑥| + 𝐶
𝑎
1
12) ∫ 𝑐𝑠𝑐𝑥 𝑑𝑥 = 𝑙𝑛|𝑐𝑠𝑐𝑥 − 𝑐𝑜𝑡𝑥| + 𝐶 12) ∫ 𝑐𝑠𝑐𝑎𝑥 𝑑𝑥 = 𝑙𝑛|𝑐𝑠𝑐𝑎𝑥 − 𝑐𝑜𝑡𝑎𝑥| + 𝐶
𝑎
1
13) ∫ 𝑠𝑒𝑐 2𝑥 𝑑𝑥 = 𝑡𝑎𝑛𝑥 + 𝐶 13) 𝑠𝑒𝑐 2(𝑎𝑥) 𝑑𝑥 = tan(𝑎𝑥) + 𝐶
𝑎
1
14) ∫ 𝑐𝑠𝑐 2𝑥 = −𝑐𝑜𝑡𝑥 + 𝐶 14) ∫ 𝑐𝑠𝑐 2𝑎𝑥 = − 𝑐𝑜𝑡𝑎𝑥 + 𝐶
𝑎
1
15) ∫ 𝑠𝑒𝑐𝑥 ∙ 𝑡𝑎𝑛𝑥 𝑑𝑥 = 𝑠𝑒𝑐𝑥 + 𝐶 15) ∫ 𝑠𝑒𝑐𝑎𝑥 ∙ 𝑡𝑎𝑛𝑎𝑥 = 𝑠𝑒𝑐𝑎𝑥 + 𝐶
𝑎
𝑑𝑢 1 𝑢
16) ∫ = tan−1 + 𝐶, 𝑢 = 𝑓(𝑥)
𝑎2 +𝑢2 𝑎 𝑎
𝑑𝑢 𝑢
17) ∫ = sin−1 + 𝐶
√𝑎2 −𝑢2 𝑎
𝑑𝑢 1 𝑢
18) ∫ = sec −1 + 𝐶
𝑢√𝑢2 −𝑎 2 𝑎 𝑎